“Salt lick potentials in Ecotourism Management of Borgu Sector”: Kainji Lake National Park, Nigeria (2020)
Ecotourism is a form of tourism undertaken to view and / or encounter wildlife in a range of settings. One of such eco-destinations in which wildlife can be viewed is salt licks. The study was undertaken at Borgu sector of Kainji Lake National Park. Data collection was carried out using systematic random sampling for the selection of salt lick sites, direct and indirect fauna observation using transect lines to determine the level of site utilization. Secondary data from the park management and laboratory analysis of salt lick, soil samples to detect the mineral compositions and richness of the licks as relevant to ecotourism activities in the park was examined. Observation revealed that the iron concentration (a trace element) is high in salt lick 1 (332.33), while the lowest was recorded in salt lick 6 (36.36).It was also revealed that the content of calcium (a major element) is high in salt lick 1 (4.22), with the least recorded in salt lick 6 (0.40). It was perceived that salt lick 3 and 4 were least utilized during the dry seasons. It is important to know that the mineral content of salt lick sites can be a factor affecting its utilization by fauna resources. It was observed that, turn-out of tourists visiting the park fluctuates; as a result of anthropogenic activities and other limiting factors.The overall benefits derived from salt licks for wildlife health,majorly through herbivores are crucial in maintaining a healthy wildlife community for their reproduction and survival.